USE OF KNOWN INDIVIDUAL MARKING IN RESEARCH AND MONITORING OF FRESHWATER TURTLE POPULATIONS - TESTING THE METHOD ON SOUTH AMERICAN SPECIES (TESTUDINES: PODOCNEMIDIDAE) - Marcelo Ândrade, Marcelo Ândrade (2024)
The marking or tagging of turtles is a widely used to facilitate the monitoring of population demography, structure, and conservation of species. Even though they are used in many studies of turtle demography, the available methods are not very efficient, except for microchips (Passive Intergraded Transponder/PIT tags); however, the latter is too expensive to be used on a large scale. Here we present a viable, cost-effective tagging alternative that uses a durable plastic cattle tag and pin. Turtles in the genus Podocnemis were tagged in the Lower-Amazon region, west of the state of Pará, Amazon, Brazil. This method is highly recommended for future work on monitoring and population structure of large species of freshwater turtles. In addition to feasibility, it can be used in the form of citizen science, as the information can be obtained by laypeople and taken to researchers and conservationists.